2013
DOI: 10.1021/jf402891s
|View full text |Cite
|
Sign up to set email alerts
|

Phenols and Ascorbic Acid in Black Currants (Ribes nigrum L.): Variation Due to Genotype, Location, and Year

Abstract: Black currant berries contain many biochemical compounds with proven or potential human health benefits. We studied the content of total and single polyphenols, ascorbic acid, soluble sugars, and titratable acidity for two advanced selections and three cultivars of black currant at two distant locations in Sweden (south: 56°06'N; north: 65°21'N) over a 3 year period. Regression analyses revealed the effect of genotype to be considerably larger than that of location and year. However, significant effects of loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
69
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 43 publications
12
69
1
1
Order By: Relevance
“…Although the influence of seasonal climatic conditions and geographic region/ location on the total polyphenol and anthocyanin content of sour cherry fruits was proved, according to some studies the impact of cultivar is probably more significant than the above-mentioned (Bolling et al 2010, Vagiri et al 2013. Five investigated sour cherry cultivars significantly differed among themselves in total polyphenol and anthocyanin content according to three-year data in two locations by the LSD test (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the influence of seasonal climatic conditions and geographic region/ location on the total polyphenol and anthocyanin content of sour cherry fruits was proved, according to some studies the impact of cultivar is probably more significant than the above-mentioned (Bolling et al 2010, Vagiri et al 2013. Five investigated sour cherry cultivars significantly differed among themselves in total polyphenol and anthocyanin content according to three-year data in two locations by the LSD test (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Interaction year × location × cultivar. Year-toyear variation in certain bioactive compounds is well investigated through a lot of species (Bolling et al 2010, Latocha et al 2013, Vagiri et al 2013). In our investigation, a significant interaction between year, cultivar and location was found (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Kaldmae et al [2013] observed that vitamin C content is negatively correlated with temperature, and positively with rainfall, while Walker et al [2010] found that black currants grown on south facing slopes that received more warmth and solar radiation contained up to 20% more vitamin C than those grown on north facing slopes. Vagiri et al [2013] reported higher levels of vitamin C in currants grown in the south of Sweden compared to currants grown in the north of Sweden. As explained by the authors, the differences were the result of a higher mean air temperature during harvest season, which was not confirmed in the present study.…”
Section: Resultsmentioning
confidence: 93%
“…The chemical composition of the fruit is governed by the genetic predisposition of cultivar [Bordonaba and Terry 2008] and maturity stage, but also to a large extent by climatic factors [Zheng et al 2009, Walker et al 2010, Vagiri et al 2013. Climatic conditions including light and average temperature have a strong influence on the chemical composition of crops [Klein and Perry 1982].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation